RETHINKING SOLIDARITY THROUGH WELFARE TECHNOLOGY FOR OLDER ADULTS - Brita Gjerstad; Inger Lise Teig (Banber Erevani Hamalsarani. Sots'iologia)
The welfare state is under pressure. Demographic changes, high expectations for services, and limited resources demand new approaches to service provision. In Norway, national authorities advocate for the use of technology and the involvement of volunteers in health and care services. This paper explores the relationship between solidarity, technology and volunteerism by asking whether the use of technology in health service delivery aligns with the values of solidarity. The empirical basis of the paper is qualitative sub-studies from the research project Caring Futures, as presented in three articles. The sub-studies reveal that technologists strongly support increased use of technology. By framing technology as a means to promote autonomy, they implicitly downplay human dependency. As a result, technology appears to conflict with a concept of solidarity rooted in mutual interaction. In contrast, relatives of nursing home residents recognise and accept dependency. Rather than attempting to eliminate it, they embrace dependency as a foundation for social connection, mutual responsibility and solidarity.